Posicionamento por ponto de alta precisão utilizando o GPS: Uma solução para a geodinâmica - Monico, J. F G [UNESP] (FapUNIFESP (SciELO), 2000)
Point positioning from GPS data can provide precision varying from 100 meters to a few millimeters at the level of 95% probability. To reach the best level of accuracy, users need proper equipment and software, as well as access capability to GPS products available at the International GPS Geodynamics Service. In this paper, the theory related to point positioning using GPS is presented as well as the results of an experiment conducted using data from the Brazilian Active Control System. The results show repeatability better than 5mm and 10mm for the N and E baseline components respectively, and 6mm + 4ppb (parts per billion) for the vertical. Comparison with SIRGAS campaign showed results at the same level of uncertainty as that of the stations used to tie the SIRGAS frame to ITRF94. Therefore, precise point positioning is a powerful tool to be used in applications requiring high level of precision, such as Geodynamics.
Point positioning of high accuracy using the GPS- a solution for geodynamics
Keywords: GPS Positioning; High Precision Positioning; Repeatability; Satellite Clock Corrections; GPS